Mathematical model of formation of two-phase zone of casting of aluminum alloy of eutectic composition, which is hardened under increasing gas pressure (Modern Problems of Metallurgy, 2019)
Analysis of thermal fields allows to obtain reliable information about the location of thermal nodes, areas with insufficient or excessive dynamics of solidification, but the calculation of the shrinkage shell and macrosparity is carried out on the basis of criterion assessments. Porosity is one of the main defects of castings, which leads to a decrease in mechanical properties. This defect arises as a result of insufficient or difficult supply of the two-phase zone; therefore, an urgent problem is the development of mathematical models for the formation of a two-phase zone of castings hardening under conditions of increasing gas pressure, in particular, casting from aluminum alloys of eutectic composition, are among the most common for the manufacture of shaped castings. The proposed mathematical model for supplying a two-phase zone of metal castings hardening under the influence of controlled gas pressure is based on a thermodynamic cell-automatic mathematical model for describing metallurgical processes with phase transitions, ensures that the changes in the thermodynamic characteristics of metals correctly take place. The power supply model of the two-phase zone allows to provide a correct account of the adjustable gas pressure in the casting-form system and can be scaled to two-dimensional and three-dimensional space. The results of modeling the process of feeding the two-phase zone of the casting of aluminum alloy of eutectic composition. The dependences of the amount of the liquid phase in local volumes in the two-phase zone.
Keywords: mathematical model; heat transfer; mass transfer; filtration; shrinkage; saliva; aluminum; eutectic composition